Compressive mechanical properties and microstructure of PVA–HA hydrogels for cartilage repair. Issue 24 (18th February 2016) - Li, Wenxu; Wang, Duo; Yang, Wen; Song, Ying
Abstract : In this paper, hydroxyapatite (HA) was deposited on poly(vinyl alcohol) (PVA) molecular chains by an in situ synthetic method. Abstract : In this paper, hydroxyapatite (HA) was deposited on poly(vinyl alcohol) (PVA) molecular chains by an in situ synthetic method. Subsequently, combining cyclic freeze/thaw treatment, PVA–HA gel composites consisting of flexible PVA and rigid HA were prepared. The phase composition and structure of the PVA–HA hydrogels were investigated by XRD, IR and SEM methods, and their compressive mechanical properties were evaluated using mechanical test equipment. The results showed that PVA provides a flexible porous network skeleton to the hydrogel. The HA particles were distributed inside the pores and on the walls of the pores, strengthening the compressive properties of the PVA–HA hydrogel. Moreover, the increased PVA and HA contents could increase the compressive modulus and compressive strength of the hydrogel. The effect of the PVA content on the compressive mechanical properties of the hydrogel was predominant, especially at high strain rates. The maximum compressive strength of the PVA–HA hydrogel was 0.43 MPa, which remained even at a compression deformation rate up to 70%. The relationship between the compressive modulus and compression ratio tended to be an exponential function, same as the trend of the stress–strain curve. The results indicate that the prepared hydrogel is a viscoelastic material, which has potential for the application of articular cartilage repair.